Daratumumab in the treatment of C3 glomerulopathy with monoclonal gammopathy: a case report and literature review - Esposito, Pasquale; Picciotto, Daniela; Costigliolo, Francesca; Russo, Elisa; Macciò, Lucia; Cenacchi, Giovanna; Cagnetta, Antonia; Cea, Michele; Lemoli, Roberto M.; Viazzi, Francesca (Frontiers in Medicine, 2023)
Although rare, C3 glomerulopathy (C3G) is increasingly recognized thanks to the currently available diagnostic skills. C3G is not a single disease but a group of disorders with distinct pathogenesis and progression. Thus, an essential step for its management remains an in-depth characterization of the specific form and the identification of underlying conditions, which may also impact treatment choices as well. Among these entities, an emerging condition is the association of C3G with monoclonal gammopathy, which confers poor outcomes. Overall, diagnosis of C3G remains challenging, and determining the appropriate treatment remains unclear. Conventional immunosuppressive therapy has proven ineffective in such cases, while clone-directed therapies have shown promising results in small interventional studies and case series. Here, we report a case of a patient affected by C3G with monoclonal gammopathy of renal significance who experienced rapid deterioration of kidney function requiring replacement therapy. After the failure of first-line treatment, a switch to the anti-CD38 therapy with daratumumab resulted in the progressive improvement of the patient’s kidney function, leading to the discontinuation of hemodialysis after approximately 10 months. Serial renal biopsies were also performed to study the disease’s evolution in response to the treatment. Based on the description of this single case, we have comprehensively reviewed available studies on daratumumab use in patients with C3G associated with monoclonal gammopathy to provide insights for the design of prospective studies which aim to enhance the management of such poor prognosis disease.